Chronic Kidney Disease, Hemodynamic Instability, and Endoscopic High-Risk Appearance Are Associated with 30-Day Rebleeding in Patients with Non-Variceal Upper Gastrointestinal Bleeding - Lee, Yoo Jin; Kim, Eun Soo; Hah, Yu Jin; Park, Kyung Sik; Cho, Kwang Bum; Jang, Byoung Kuk; Chung, Woo Jin; Hwang, Jae Seok (Journal of Korean medical science, 2013)
The results of studies that evaluated predictive factors for rebleeding in non-variceal upper gastrointestinal bleeding are inconsistent. The aim of this study was to investigate predictive factors for 30-day rebleeding in these patients. A consecutive 312 patients presenting symptoms and signs of gastrointestinal bleeding were enrolled in this prospective, observational study. Clinical and demographic characteristics and endoscopic findings were evaluated for potential factors associated with 30-day rebleeding using logistic regression analysis. Overall, 176 patients were included (male, 80.1%; mean age, 59.7±16.0 yr). Rebleeding within 7 and 30 days occurred in 21 (11.9%) and 27 (15.3%) patients, respectively. We found that chronic kidney disease (CKD) (OR, 10.29; 95% CI, 2.84-37.33; P<0.001), tachycardia (pulse>100 beats/min) during the admission (OR, 3.79; 95% CI, 1.25-11.49; P=0.019), and Forrest classes I, IIa, and IIb (OR, 6.14; 95% CI, 1.36-27.66; P=0.018) were significant independent predictive factors for 30-day rebleeding. However, neither Rockall nor Blatchford scores showed statistically significant relationships with 30-day rebleeding in a multivariate analysis. CKD, hemodynamic instability during hospitalization, and an endoscopic high-risk appearance are significantly independent predictors of 30-day rebleeding in patients with non-variceal upper gastrointestinal bleeding. These factors may be useful for clinical management of such patients.